Media narration, group behaviour, and nationalistic response to China’s photovoltaics on Bilibili - Zha, Yiru (2023)
The escalating rivalry between the US and China in the photovoltaics industry has brought increased attention to Chinese nationalism towards the industry. This study examines how media narration and group behavior are associated with nationalist responses to China’s photovoltaics, using 4558 comments and 11 video texts related to the geopolitical issues of China’s photovoltaics on the Bilibili platform. By applying ordinal logit, OLS, and ARMA regression analyses, this study finds that: (1) Nationalism in the comment zone tends to be positively associated with media’s narration of the West’s crackdown on China’s photovoltaics, blaming of Western countries and labeling of the West as a hegemonic force compared to China. (2) Nationalism in the comment zone tends to be negatively associated with the media’s narration of China’s photovoltaics’ strengths and achievements and its counterstrike against the West. (3) Media’s narration of China PV’s deficiencies and its capitalism-socialism narrative framework are insignificant to nationalism in the comment zone. (4) A cycle of conformity and anticonformity of nationalism emerges over time, demonstrating the strengthening of internal consistency and divergence among various internet groups. While complementing the existing literature, this study provides policy insights into controlling cyber nationalism by reducing blaming discourses, identity antithesis in narrations, and polarization of political sentiment.